Por uma clínica cartográfica do trabalho. - Bezerra, Maria de Lourdes Cordeiro de Araújo (2023)
Neoliberalism has produced major changes in society, engendering specific criteria of truth and a new ethos, a new aesthetics of existence guided by widespread competition and I-company ideology. These changes in the working world, initially very evident in private companies, ended up becoming a reality in government agencies, leading to changes in governance models and, therefore, in modes of subjectivation of public servants. In this context and in parallel with the challenges faced by public service nowadays, which include adherence to management practices in tune with neoliberalism, we deal with a situation in an agency of the Federal Judiciary Power in which the number of days of sick leaves has increased, these sick leaves being associated with ICD F – nosological category of behavioral and mental disorders. In an attempt to understand the situation, we endeavored some actions related to the health department of the agency, which culminated in the implementation of a clinical hearing of working communities inside the agency. The intervention-research, object of the present work, takes place in this context and was carried out in 2017 with a group of seven civil servants who carried out nine group sessions. Six previous sessions had been already carried out, some of them with management staff of the agency. The study is based in Cartography as a theoretical-methodological approach and aimed to analyze this intervention-research project in search of understanding the resulting resonances of this clinical practice. For this purpose, we tried to examine how the spread of neoliberalism has impacted the working world, the Brazilian State and, more specifically, our nation’s judicial system; to map the cartographic paths which emerged during the work; and understand what are the contributions of the interventional process for the prevention of mental health of the participant collective, with repercussions within the research institution. Since Cartography does not have a methodology with predetermined guiding steps, being developed throughout the process, we followed paths, clues, and footprints which were found throughout the investigation. From some previously known conceptual cartographic paths, as well as from their entanglements, we produced others which indicated: the direction of the hearing process and other steps to be followed from whatever stemmed in the course of the investigation; the necessity of mapping the path that constitutes us in a way that our historicity is not lost; also, to confirm Cartography as an approach which brings an ethical-aesthetical policy in the clinical hearing in the working environment. We concluded by understanding that the work, which was carried out through this theoretical-methodological perspective to Cartography, enabled among other things, to: a broader understanding that constraints in the labor context were related to the organization of work and somehow affected the whole working community; pave way to discussions and collective deliberations in relation to labor issues that affected the group; produce implications, in view of the need to take us assume a clear stand before oppressive conditions and life degradation in its various aspects, all of them reverberating in institutions. Thus, we sustain that clinical cartographical hearing of work groups, carried out by a collective of clinics in equal conditions, is able to produce micro-political shifts in favor of the mental health of the community subjected to the hearing process, reverberating, above all, in the health prevention area and resonances in the agency subject to the present research.